Language as an institution: A note on the use of the terms finance and economics in the Greek language and its consequences for the Greek society and economy - Elias Sanidas (SPOUDAI - Journal of Economics and Business, 2020)
Language as a formal and informal institution can be a useful tool of the society for effective communication in order to adopt the right policies for economic development, etc. And yet Greece is probably the only country in the world which does not differentiate Finance from Economics, e.g. people say "my oikonomika" (economics) in order to mean "my finance"; or the accountant calls himself economist (oikonomologos); or the Minister of Economic(s) should be called the Minister of Money, etc. Thus, almost everybody in Greece talks about money but almost nobody talks about the economy. And yet the economy which is primarily growth in effective and efficient production should be our primary concern, and not money, unless it is used for investment. The present confusion of finance and economics words and concepts in Greece is shown in this paper; also, its negative consequences; its relations with prominent economic models; and suggestions for removing this institutional backwardness in Greece.
Keywords: B52; B10; B20; 330; institutions; language; finance; money; economics; Greece